EFFORT TO IMPROVE ACTIVITIES, SOCIAL STUDIES STUDY RESULT, AND IMPLEMENTATION OF THE INTEGRATED NATION CHARACTER EDUCATION VALUES BY COOPERATIVE STUDY JIGSAW TYPE AT THE FIFTH GRADE STUDENTS OF SDN 126 BAYAN SURAKARTA YEAR 2011 - Suwarto, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
The main objectives of Class Action Research are: (1) To improve student activities in Social Studies learning by Jigsaw type cooperative study implementation for the fifth grade students of SDN 126 Bayan Surakarta Year 2011. (2) To improve the social studies learning result by implementing the Jigsaw type cooperative study for the fifth grade students of SDN 126 Bayan Surakarta Year 2011.(3) To review the improvement of Educational value of Nation Character Jigsaw type cooperative study for the fifth grade students of SDN 126 Bayan Surakarta Year 2011. The research subject is 47 fifth grade students of SDN 126 Bayan Surakarta which consist of 24 male students and 23 female students.Based on the research result, it may be concluded that: (1) The activities of social studies (IPS) learning at the fifth grade students of SDN 126 Bayan has increased. It is proven by the increase of student activities scores at the average of 2.3 in cycle I, and 3.3 in cycle II. (2) Social studies learning resulted by Jigsaw type cooperative study for the fifth grade students of SDN 126 Bayan Surakarta has increased as proven by the initial condition at the average of 63.4 with a classical completeness percentage of 49%. In the cycle I the average grade was 67, 2, with the classical completeness percentage of 68.1%. In the second cycle, the class average grade increased to 76.7, with the classical completeness percentage of 100%. (3) The Nation Character Education Values on elementary students in SDN 126 Bayan has increased. This is proven by the average grade of the cycle I, which was 54.31, has increased to 67.63 in the second cycle. Jigsaw Cooperative learning is one type of effective learning to enhance students› activity. The more active students will improve their thinking power which result in an increase of the students’ learning outcomes, including the increase of educational value of the nation›s character.